Implementasi Kebijakan Program Pembinaan Anak Terlantar di Kecamatan Indralaya Utara Kabupaten Ogan Ilir - Ariska, Lilis; Alamsyah, Alamsyah; Junaidi, Junaidi (Jurnal Dinamika Manajemen dan Kebijakan Publik (DMKP), 2021)
This study aims to find out implementation factors and describe the performance of the implementation of the policy of abandoned Child Development Program in North Indralaya Subdistrict, Ogan Ilir Regency. The type of research used is a qualitative descriptive research type with data collection techniques in the form of observations, interviews, and documentation. Data analysis and reduction techniques using Atlas.ti. The results showed that all indicators of the policy implementation model of Van Meter and Van Horn (1975) have not been achieved as a measure of the success of the policy implementation process of the abandoned Child Development Program in North Indralaya Subdistrict, Ogan Ilir Regency. This study uses the theory of policy implementation of Van Meter and Van Horn (1975) and output policy performance from Purwanto (2012). The results showed the performance of the implementation of the policy of the Abandoned Child Development Program in North Indralaya Subdistrict, Ogan Ilir Regency is already achieved but has not been fully maximized. Good implementation factors that affect the policy are standards and policy objectives, policy resources, communication between organizations and various strengthening activities, social, economic and political conditions, characteristics of implementing agents and disposition of implementors. The results showed that the policy of abandoned Child Development program in North Indralaya Subdistrict of Ogan Ilir Regency has not been maximized due to low budget resources, resulting in the implementation of the policy has not fully met the standards. Research also shows that there is no local regulation or the like at the regional level that regulates the problem of displaced children in the Ogan Ilir area and judging by the performance of its output that indicators of access, coverage and bias are also still not optimal because it is influenced by standard factors and policy objectives and policy budgetresources.